Improving Students’ Speaking Skills by Story Telling - Caroline Sabatiana Ambarita; Junita Siahaan; Resperdiana Purba; Irma Khoirot Daulay (INTERACTION: Jurnal Pendidikan Bahasa, 2023)
Listening, speaking, writing, and reading are four activities that encourage each other in the communication process, known as the four skills language. When one of the four Language Skills speaks, it takes center stage. This student needs more opportunities to speak English in public, either at or outside of school. Students not used to communicating in English could struggle to compete with international students. Language is also regarded as a difficult lesson by students because they become easily bored during the learning process. This factor influences participants' desire to study English at a higher level. Lessons are uninteresting to students, and as a result, they need to accept learning optimally. Researchers use survey results to collect student responses to learn how to use storytelling to improve students' language skills. Ten students from MIPA-1 SMAS Yayasan Pendidikan Pangeran Antasari Class X Participant research is in the works. The questionnaire responses are reviewed and revised to produce reliable results. According to research findings, 90% of students are satisfied with their English language lessons, while 60% of dissatisfied students believe that English language lessons are too difficult. Approximately 90% of English students, particularly those enrolled in the Skills Speak course, are overjoyed. The brave student has only completed half of his in-class English speaking.